Breast cancer patient with everolimus-induced angioedema: A rare occurrence with potential for serious consequences. (June 2017) - Roe, Neil; Twilla, Jennifer D; Duhart, Benjamin; Wheeler, Brian
Background: The development of angioedema is a rare yet serious clinical event that may develop due to an adverse drug reaction. Rapid recognition and treatment of this adverse reaction is critical for optimal patient outcomes; however, prevention of this occurrence is preferred. Case report: A 59-year-old woman presented to the emergency department with lingual angioedema caused by the addition of everolimus to her medication regimen. The patient improved after withdrawal of the offending agent and standard treatment. Early recognition by healthcare providers and management of everolimus-induced angioedema is vital for successful patient outcomes. This report increases awareness of everolimus as a potentially causative agent for the development of angioedema.